Optimizing performance parameters of stationary wire free power transfer circuit - Raja Vidya; Belur K. Keshavan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The power efficiency of the wire free power transmission (WPT) system is tested in this article under various transmission distance circumstances, and the findings are utilized to investigate the best way to regulate the parameters for charging electric vehicles (EVs). The system`s power transfer efficiency is improved over using a fixed resonant frequency by altering it in response to changes in the coupling coefficient. In relation to resonance frequency, a trade-off between output power magnitude and power efficiency is also revealed. Through numerical simulation with Ansys, the trade-off resonant frequencies at various transmission lengths are determined by the analysis. Here, the transmitter and receiver employ circular coils with a circular cross-sectional area and a straightforward but effective series-series (SS) compensation architecture is used for comprehensive analysis.